Pembuatan Sistem Informasi Penjualan Pada TOKO RAKA - Wahyuningsih, Ipin; Purnama, Bambang Eka; Wardati, Indah Uly (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
ABSTRACT: At Raka Store, recording and processing of data items, the number and price of the goods, the supplier of data, as well as the sales transaction data is still done using handwriting. Difficulty in recording and counting the number of types of goods, quantity of goods, as well as the large number of prices, resulting in the data obtained to be less accurate. To improve the accuracy of the data, the system required the development of a computerized information goods sales. Application is made by selling goods using PHP as a maker of software main interface and MySQL as its database. This program allows the user to input the data, edit data, delete data, data retrieval, data filtering and data printing to paper media. The data entered in the form of goods data, supplier data, the data type of the data item and the sale of goods. While the output is in the form of information system reports data items, reports supplier data, sales data and memorandum items the sale of goods. Application is the sale of goods can be one solution that can be used to facilitate the seller in the sale of goods data processing, and reporting of data items, supplier data reports, reports sales of goods, as well as a memorandum of the sale of goods becomes easier, faster and efficient. Keywords: sales information system Abstraksi : Pada Toko Raka, pencatatan dan pengolahan data barang, jumlah dan harga barang, data para supplier, serta data transaksi penjualan masih dilakukan dengan menggunakan tulisan tangan. Kesulitan dalam mencatat dan menghitung banyaknya jenis barang, jumlah barang, maupun besarnya jumlah harga, mengakibatkan data yang diperoleh menjadi kurang akurat. Untuk meningkatkan keakuratan data, diperlukan pembangunan sistem informasi penjualan barang yang terkomputerisasi. Aplikasi penjualan barang ini dibuat dengan menggunakan software PHP sebagai pembuat interface utama dan MySQL sebagai basis datanya. Program ini memungkinkan user untuk input data, edit data, hapus data, pencarian data, penyaringan data dan pencetakan data ke media kertas. Data yang diinputkan berupa data barang, data supplier, data jenis barang dan data penjualan barang. Sedangkan output yang dihasilkan sistem informasi ini berupa laporan data barang, laporan data supplier, data penjualan barang dan nota transaksi penjualan barang. Aplikasi penjualan barang ini dapat menjadi salah satu solusi yang dapat digunakan untuk mempermudah penjual dalam mengolah data penjualan barang, dan membuat laporan data barang, laporan data supplier, laporan penjualan barang, serta nota transaksi penjualan barang menjadi lebih mudah, cepat dan efisien. Kata Kunci : Sistem informasi penjualan